1993
DOI: 10.1021/bi00054a022
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of PR8 influenza virus through the octadecylrhodamine B chloride membrane marker

Abstract: The octadecylrhodamine B chloride (R18) membrane marker was incorporated into PR8 influenza viruses and virus receptor (GD1a-) containing small unilamellar vesicles (SUV). Both were tested in a fusion/lipid transfer assay [Wunderli-Allenspach, H., & Ott, S. (1990) Biochemistry 29, 1990-1997] to find out whether incorporation into artificial and biological membranes yields equivalent results. The R18 assay is based on incorporation of quenched concentrations of the label into donor membranes and monitoring of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
3
14
2
Order By: Relevance
“…This level of reduced infectivity is consistent with infectivity losses reported for other R-18-labeled viruses (24). We next demonstrated that H. virescens midgut cells could become saturated with R-18-labeled ODV and that labeled ODV binding could be reduced progressively by the addition of increasing amounts of excess unlabeled ODV.…”
Section: Discussionsupporting
confidence: 89%
“…This level of reduced infectivity is consistent with infectivity losses reported for other R-18-labeled viruses (24). We next demonstrated that H. virescens midgut cells could become saturated with R-18-labeled ODV and that labeled ODV binding could be reduced progressively by the addition of increasing amounts of excess unlabeled ODV.…”
Section: Discussionsupporting
confidence: 89%
“…As a π ‐system with delocalized positive charge, R18 may act as a transporter of molecules with likewise delocalized anionic charges into and across phospholipid bilayers . Dramatic effects of R18 and other membrane markers have been observed in investigations of viral membrane fusion, all the way to inactivation of the PR8 influenza virus . Finally, fluorescent lipid probes have been shown to generate light‐induced artifacts under laser irradiation of confocal fluorescence microscopy experiments …”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…[29] Dramatic effects of R18 and other membrane markers have been observed in investigations of viral membrane fusion, all the way to inactivation of the PR8 influenza virus. [30] Finally, fluorescent lipid probes have been shown to generate lightinduced artifacts under laser irradiation of confocal fluorescence microscopy experiments. [31 -34] In summary, and in agreement with our experimental result, we must state that these fluorescent dyes are by no means 'innocent' labels, and that 'caution is needed when using direct labeling of biological membranes'.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The lipid-mixing assay may indicate that the hairpin conformation, which is the point at which lipid mixing occurs, is achieved in the presence of these antibodies and that palivizumab and motavizumab block the transition from a hairpin conformation to a postfusion conformation. However, several reports suggest that R18 can passively transfer from virus to target cell by shear proximity of the membranes (5,36,46,54,55). Therefore, it is possible that R18 may transfer from virus to target cell upon the initial interaction of the F protein with the target cell membrane or the prehairpin conformation.…”
Section: Discussionmentioning
confidence: 99%